Cannabidiol attenuates delayed-type hypersensitivity reactions via suppressing T-cell and macrophage reactivity - Liu Der-zen; Hu Chieh-min; Huang Chung-hsiung; Wey Shiaw-pyng; Jan Tong-rong (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects cannabidiol (CBD) on delayed-type hypersensitivity (DTH) reactions and antigen-induced T-cell cytokine expression. Methods: DTH was induced by subcutaneous ovalbumin (OVA) challenge to the footpads of mice sensitized with OVA. Inflammatory reactions were measured by footpad swelling and histological analysis. Antigen-induced cytokine expression by OVA-primed splenocytes was measured using ELISA and RT-PCR. Results: CBD (1-10 mg/kg) administration, in a dose-dependent fashion, significantly attenuated inflammatory reactions associated with DTH in the footpads of mice sensitized and challenged with OVA. Histological examination revealed that CBD suppressed the infiltration of T cells and macrophages, and the expression of interferon (IFN)-γ and tumor necrosis factor-α, two pro-inflammatory cytokines implicated in DTH in the inflammatory site. In contrast, the expression of interleukin (IL)-10 in the footpads was enhanced by CBD administration. In addition, CBD at concentrations devoid of cytotoxic effects (1-4 μmol/L) attenuated OVA-induced IFN-γ production by OVA-primed splenocytes, whereas IL-4 was unaffected. Conclusion: CBD curbs DTH reactions via suppressing the infiltration and functional activity of T cells and macrophages in the inflammatory site, suggesting a therapeutic potential for CBD for the treatment of type IV hypersensitivity.